Would edible insects become part of our gastronomic quest? - Jagadeesan, Premanandh; Siddiqui, Abdullah; Muzahem, Salem; Jaber Mohamed Al Shareef, Ahmed (Edelweiss Applied Science and Technology, 2024)
Global food security status has been contested in recent times with claims of efficient food production by the proponents and severe to moderate food insecurity by the opponents. The current population growth prediction of 9.7 billion by 2050 requires additional food production due to the impact of climate change leading to diminished yield rates. Novel food sources such as cellular agriculture utilizing modern biotechnology are at various trial and commercialization stages. Old traditions of insects as a reliable food (entomophagy) source are gaining momentum in recent times. This article explores various aspects of entomophagy. The ecological footprint of entomophagy on its animal counterparts is presented. Since religious factors have a major impact on eating habits that privileges certain elements, perspectives from major religions on entomophagy have been discussed. The regulatory standpoint of Anglo-Saxon, Western and Eastern societies are given. Consumer knowledge and commercialization challenges are also discussed with concluding remarks.